People’s Participation in forestry Sector - an Approach - Singh, Jarnail (Indian Forester, 1994)
People’s participation in all aspects of forestry sector is one of the cherished goals, defined in National Forest Policy. The emphasis, to this aspect was given time and again but integrated and defined approach have not been evolved to ensure willing co-operation and active involvement of local inhabitants, baring a few area-specific trials. A systematic and defined approach was formulated and initiated in East Melghat Forest Division Amarvati (Maharashtra State) to ensure co-operation and involvement of local inhabitants in the forestry sector. The approach is yet in initial stages. It is gradually taking roots in the psyche of the people and the field staff and the ensuing out comes are encouraging.